PENERAPAN TERAPI BEKAM BASAH PADA NY. H DALAM MENURUNKAN SKALA NYERI PASIEN LOW BACK PAIN DI KLINIK ZEIN HOLISTIC THERAPY - Sarmila Sarmila; H. Samsualam; Eliati Paturungi; Sunarti Sunarti (CV. Adiba Aisha Amira, 2025)
Wet cupping is a complementary method widely applied to alleviate pain by enhancing circulation, relaxing tissues, and reducing inflammatory mediators. This case report examines the application of wet cupping in a patient with lower back pain. Post‑intervention assessment showed a notable decrease in pain intensity and improved patient comfort, indicating its potential as an effective non‑pharmacological option.